Impact of nasal ventilation on survival in hypercapnic Duchenne muscular dystrophy. Issue 11 (1st November 1998) - Simonds, A K; Muntoni, F; Heather, S; Fielding, S
Abstract : BACKGROUND: Respiratory failure is the commonest cause of death in patients with Duchenne muscular dystrophy (DMD). Life expectancy is less than one year once diurnal hypercapnia develops. This study examines the effects of nasal intermittent positive pressure ventilation (NIPPV) on survival in symptomatic Duchenne patients with established ventilatory failure. METHODS: Nocturnal NIPPV was applied in 23 consecutive patients with DMD of mean (SD) age 20.3 (3.4) years who presented with diurnal and nocturnal hypercapnia. RESULTS: One year and five year survival rates were 85% (95% CI 69 to 100) and 73% (95% CI 53 to 94), respectively. Early changes in arterial blood gas tensions following NIPPV occurred with mean (SD) Po 2 increasing from 7.6 (2.1) kPa to 10.8 (1.3) kPa and mean (SD) Pco 2 falling from 10.3 (4.5) kPa to 6.1 (1.0) kPa. Improvements in arterial blood gas tensions were maintained over five years. Health perception and social aspects of SF-36 health related quality of life index were reported as equivalent to other groups with non-progressive disorders using NIPPV. CONCLUSION: Nasal ventilation is likely to increase survival in hypercapnic patients with Duchenne muscular dystrophy and should be considered as a treatment option when ventilatory failure develops.